α2-Adrenoreceptor Status of Human Platelet Subpopulations Separated by Continuous Flow Electrophoresis - Crook, M; Crawford, N (Thrombosis and Haemostasis, 1993)
Human platelets were separated into subpopulations using continuous flow electrophoresis, which uses electrophoretic mobility as the separative parameter. The platelets with the greatest electrophoretic mobility showed higher amounts of total sialic acid than the less electrophoretically mobile subpopulation (74.3 ± 18.2 nmol/109 platelets vs. 49.2 ± 20.1 nmol/109 platelets, p <0.05 paired Student’s t-test). Furthermore, neuraminidaselabile sialic acid was also elevated in the more electrophoretically mobile platelet subpopulation (29.1 ± 6.0 nmol/109 platelets vs. 21.8 ± 10.4 nmol/109 platelets, p <0.05 paired Student’s t-test). We also found that the sialic acid enriched platelet subpopulation had more α2-adrenoreceptors than the less electrophoretically mobile platelets (457 ± 104 vs. 302 ± 164 receptors per cell, p <0.05 paired Student’s t-test).